2005
DOI: 10.1021/jf050570o
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Urine Responses Are Lower for Acylated vs Nonacylated Anthocyanins from Raw and Cooked Purple Carrots

Abstract: The bioavailability of acylated vs nonacylated anthocyanins and the effect of cooking and dose on the comparative bioavailability were investigated in a clinical feeding study using purple carrots as the anthocyanin source. Treatments were purple carrots as follows: 250 g raw (463 micromol of anthocyanins: 400 micromol acylated, 63 micromol nonacylated), 250 g cooked (357 micromol of anthocyanins: 308.5 micromol acylated, 48.5 micromol nonacylated), and 500 g cooked (714 micromol of anthocyanins: 617 micromol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
153
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 44 publications
19
153
1
Order By: Relevance
“…Thus, compound 1 was an 8-epimer of 11-O-acetyl-8-epi-torilolone 8-O-b-D-glucopyranoside isolated from the methanolic extract of Torillis japonica D. C. fruit. 20) In addition, the deacetate derivative of the aglycone (1b) obtained using acid hydrolysis of 1, was revealed to be torilolone by comparison of its 13 C-NMR data (Table 1) with those previously reported. 20) This suggestion was supported by the downfield shifts of C-6 (by Ϫ3.8 ppm), C-7 (by Ϫ5.3 ppm) and by the upfield shifts of C-12 (by ϩ3.0 ppm), when compared with those of 8-epi-torilolone.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, compound 1 was an 8-epimer of 11-O-acetyl-8-epi-torilolone 8-O-b-D-glucopyranoside isolated from the methanolic extract of Torillis japonica D. C. fruit. 20) In addition, the deacetate derivative of the aglycone (1b) obtained using acid hydrolysis of 1, was revealed to be torilolone by comparison of its 13 C-NMR data (Table 1) with those previously reported. 20) This suggestion was supported by the downfield shifts of C-6 (by Ϫ3.8 ppm), C-7 (by Ϫ5.3 ppm) and by the upfield shifts of C-12 (by ϩ3.0 ppm), when compared with those of 8-epi-torilolone.…”
Section: Resultsmentioning
confidence: 68%
“…A careful analysis of their NMR spectra suggested that two compounds 1 and 2 were closely related guaiane-type sesquiterpenoids. [21][22][23][24] In comparison with 1, the resonance signals of 2 for an acetoxy group and one methine disappeared in the 1 H-and 13 C-NMR spectra, but one more oxygenated quaternary carbon at d C 80.8 (C-1) appeared in the 13 C-NMR spectrum. In addition, the anomeric carbon at d C 98.6 was shifted by Ϫ6.3 ppm than that of 1, suggesting that a b-glucopyranosyl moiety of 2 was attached to the tertiary alcohol group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when the amount of ingested cooked carrots was increased from 250 to 500 g, neither C max nor AUC values were affected. Accordingly, the relative urinary recovery of the higher dose was significantly smaller, thus suggesting that anthocyanin absorption capacity was already saturated at the higher dose [59].…”
Section: Anthocyaninsmentioning
confidence: 95%
“…In modern pharmacological research, it has exhibited a wide range of pharmacological effects, including antibacterial [2], antifungal [3], anthelmintic, hepatoprotective [4], and cytotoxic [5] activities. Previous chemical investigations on the plant of D. carota have demonstrated the occurrence of sesquiterpenes [6], chromones [7], flavonoids [8], coumarins [6a] [9], and anthocyanins [10]. As a part of our continuous investigation on bioactive constituents [11], we initiated a chemical investigation of this plant.…”
mentioning
confidence: 99%